USING 3D VIRTUAL ACTIVITIES TO CONDUCT COLLABORATIVE WORK - Somaratne, Punsisi; Ortega, Maricarmen Gil; Falconer, Liz (PEOPLE: International Journal of Social Sciences, 2019)
Collaborative work can be conducted either in a classroom environment or in a computer-supported environment. The virtual world is one such computer supported environment that is used to conduct group activities. In this study, we explore students’ experiences in 3D virtual group activities. We conducted this study with the first-year Information Technology students in a Sri Lankan higher education institute. We planned this study in two steps; in the first step, we explored students’ experiences in classroom collaboration. After that, in the second step, we explored students’ experiences in virtual collaboration. Finally, we compared the results gathered from the questionnaire and found that students had a positive attitude about virtual collaboration compared to classroom collaboration. Moreover, we analysed the interview data qualitatively and identified students’ views about classroom group work and virtual group work. After analysing the data, we identified that students prefer to work in virtual group work than classroom group work. Also, it was clear that students’ participation and active engagement in virtual group activities were higher than classroom group activities. Based on these findings, we conclude that students had a positive experience in virtual group work.